2009
DOI: 10.1097/qad.0b013e32831fb540
|View full text |Cite
|
Sign up to set email alerts
|

A frequent functional toll-like receptor 7 polymorphism is associated with accelerated HIV-1 disease progression

Abstract: This is the first report of a functional TLR7 variant to be associated with susceptibility to and a more severe clinical course of HIV-1 disease. These results may have implications for the risk assessment of individual patients as well as for HIV-1 therapy and vaccination strategies in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 66 publications
4
89
3
Order By: Relevance
“…These are the only reported effects of the SNP at the protein/cellular level and these data were mostly (for livers), or completely (for pDCs), derived from hemizygous males. As stated above, however, most reported clinical effects of the SNP are observed in females (Oh et al, 2009;Schott et al, 2007b). We also identified effects of the SNP only in females.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…These are the only reported effects of the SNP at the protein/cellular level and these data were mostly (for livers), or completely (for pDCs), derived from hemizygous males. As stated above, however, most reported clinical effects of the SNP are observed in females (Oh et al, 2009;Schott et al, 2007b). We also identified effects of the SNP only in females.…”
Section: Discussionmentioning
confidence: 66%
“…In both infections, the variant allele associated with higher disease prevalence and augmented disease progression, and with reduced response to IFNα-therapy for HCV (Oh et al, 2009;Said et al, 2014;Askar et al, 2010;Schott et al, 2007b;Fakhir et al, 2018). In all these studies, effects were most prominent in (mostly rs179008 heterozygous) females and all studies predominantly contained Caucasian individuals.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A loss-offunction TLR7 polymorphism is correlated with elevated viral loads and a more rapid progression to disease (42). Studies have also shown that a more potent IL-10 response during acute HIV-1 infection is correlated with lower set points and reduced pathogenesis (43,44).…”
Section: Discussionmentioning
confidence: 99%